2014
DOI: 10.1007/s10597-014-9750-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Depressive Symptoms Among Hispanic/Latinos Receiving a Culturally Tailored IMPACT and Problem-Solving Intervention in a Community Health Center

Abstract: The present study investigated whether a culturally-tailored problem-solving intervention delivered by a trained depression care specialist (DCS) would improve depressive symptoms over a six month period among Hispanic/Latino patients in a federally-qualified community health center by the California-Mexico border. Participants included 189 low income Hispanic/Latino patients of Mexican heritage. Based on the Improving Mood-Promoting Access to Collaborative Treatment (IMPACT) evidence-based treatment, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Two recent, relatively large OLT ( N =189 and N = 117) demonstrated the efficacy of PST among Latinos within community health centers and rural primary care clinics (Camacho et al, 2014; Schmaling & Hernandez, 2008). Contrary to PST RCT, both of these trials showed high attrition rates, with less than 20% of participants completing treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent, relatively large OLT ( N =189 and N = 117) demonstrated the efficacy of PST among Latinos within community health centers and rural primary care clinics (Camacho et al, 2014; Schmaling & Hernandez, 2008). Contrary to PST RCT, both of these trials showed high attrition rates, with less than 20% of participants completing treatment.…”
Section: Resultsmentioning
confidence: 99%
“…While new growth communities face a number of service challenges that must be addressed for an intervention to succeed, towns that bordered the United States and Mexico confront a unique set of problems related to cyclical migration and a hostile political climate for immigrants, particularly those who are undocumented (Lapeyrouse et al, 2012;Martínez-Donate et al, 2014). For example, we excluded two studies conducted in border towns (Camacho et al, 2015;Simoni et al, 2013) because they did not report the immigration status of their participants despite the fact that interventions were offered in Spanish. We contacted these authors for clarification of their sample; one reported that they chose not to ask participants about their nationality.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitivity analysis was also conducted to assess the association of language and ethnicity on psychotherapy or pharmacotherapy depression treatment as standard of care recommendations after controlling for age, gender, and race in the first block. The model was not a significant fit to the data 2 Table 3).…”
Section: Chart Reviewmentioning
confidence: 93%